Turner Classic Movies presents Leonard Maltin's classic movie guide - Edelman, Rob; Green, Spencer; Maltin, Leonard; Scheinfeld, Michael; Weaver, Tom (Plume, 2015)
"Thanks to Netflix and cable television, classic films are more accessible than ever. Now co-branded with Turner Classic Movies, Leonard Maltin's Classic Movie Guide covers films from Hollywood and around the world, from the silent era through 1965, and from The Maltese Falcon to Singin' in the Rain and Godzilla, King of the Monsters! Thoroughly revised and updated, and featuring expanded indexes, a list of Maltin's personal recommendations, and more than two hundred new entries - including many offbeat and obscure films - this new edition is a must-have companion for every movie lover."--Pengin Books website.